KONTRIBUSI CSR PT BEHAESTEX TERHADAP PENGELOLAAN LIMBAH INDUSTRI DAN KELESTARIAN LINGKUNGAN DI PEKALONGAN - Primayanti, Asih; Titi Nur Khasanah (LPPM IAI Almuslim Aceh, 2025)
This study aims to explore the contributions of Corporate Social Responsibility (CSR) initiatives by PT Behaestex towards industrial waste management and environmental sustainability in Pekalongan. Utilizing a qualitative research approach, the study employs direct interviews as the primary method for data collection. Key stakeholders, including company management, employees, and local community members, were interviewed to gain insights into the effectiveness and impact of CSR programs implemented by PT Behaestex. The findings reveal that the company's CSR initiatives significantly enhance waste management practices, promote recycling, and foster community engagement in environmental conservation efforts. Additionally, the study highlights the importance of collaboration between the company and local communities in achieving sustainable environmental outcomes. The results underscore the role of CSR in not only mitigating the environmental impact of industrial activities but also in promoting a culture of sustainability within the community. This research contributes to the understanding of how corporate initiatives can align with environmental stewardship and community welfare, providing a model for other industries in similar contexts.